Chapter 12 The Genesis of Behaviorally Modern Homo sapiens A Cognitively Advanced Human That Can Reflect Upon Its Existence - Theroux, Steven J. (Taylor & Francis, 2023)
This book is a "big history" of the evidence regarding how we came to be. It briefly explores philosophical thought and how our past might affect our future. The text summarizes different perspectives, including the strengths and weaknesses of each. The genesis of our planet is explored, especially the circumstances that must exist for complex life to arise. This brief journey highlights the history of life, the emergence of simple lifeforms, and the evolution of complex creatures, including humans. The book concludes with a discussion of why other humanoids went extinct while our species achieved dominance. The author speculates on potentialities awaiting humankind and our planet.